Mortality and exploitation of Paradise Shelduck - Williams, Murray (Wildfowl, 1972)
Two apparently discrete populations of Paradise Shelduck Tadorna variegata were studied in New Zealand. Of 6,866 banded when moulting at 15-18 months or older, 1,143 were reported shot. Weighted mean annual mortality after 15-18 months for all years in one population was 36.4% for males and 35.0% for females; for the other 39.5% and 43.0%. The recovery rate for females was lower than males indicating they are less likely to be shot. Year-of-banding recovery rate (%) is shown to be an unreliable statistic for monitoring the intensity of shooting. In the absence of reliable data, crippling losses and non-return of bands were arbitrarily estimated to be 10% and 33% respectively, but reasons are given for believing these estimates considerably understate the true situation. In half the adult pairs raise six young per pair to fledging, a stable situation can only result if mortality from fledging to banding is less than 57% for one population and 44% for the other. Mortality rates are compared with those of other waterfowl hunted in New Zealand and other shelducks. Both populations are declining and shooting pressure should be reduced until population stability is achieved. Ways of doing this are discussed.